2011
DOI: 10.1037/a0023794
|View full text |Cite
|
Sign up to set email alerts
|

Sharing morphemes without sharing meaning: Production and comprehension of German verbs in the context of morphological relatives.

Abstract: We investigated the impact of derived German verbs on the production and recognition of morphologically related simple verbs. In order to disentangle effects of morphological, semantic, and phonological relatedness, target verbs were combined (e.g., zählen--to count) with four context verbs: Two morphologically related context verbs that were either semantically transparent (verzählen--to miscount) or semantically opaque (erzählen--to tell), a semantically related (rechnen--to calculate) and a phonologically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 111 publications
5
21
0
Order By: Relevance
“…These results are in agreement with many behavioral priming studies showing a lack of priming for morphologically complex, semantically opaque words (Feldman & Soltano, 1999;Feldman et al, 2002Feldman et al, , 2004Gonnerman et al, 2007;Longtin et al, 2003;Marslen-Wilson et al, 1994;Rastle et al, 2000;Zwitserlood et al, 2005). However, in several morphological priming studies (Luttmann et al, 2011;Smolka et al, 2009), German opaque complex verbs did give evidence of being decomposed by native speakers of German. One could hypothesize that this discrepancy is due to the task being used: Perhaps decomposition of opaque complex verbs was induced by the morphological priming technique (in which, e.g., a prime like reheat is followed by a target like heat) used in these studies.…”
Section: Cognate Verb Subdesign: Holistic Processing Of Opaque Complesupporting
confidence: 91%
“…These results are in agreement with many behavioral priming studies showing a lack of priming for morphologically complex, semantically opaque words (Feldman & Soltano, 1999;Feldman et al, 2002Feldman et al, , 2004Gonnerman et al, 2007;Longtin et al, 2003;Marslen-Wilson et al, 1994;Rastle et al, 2000;Zwitserlood et al, 2005). However, in several morphological priming studies (Luttmann et al, 2011;Smolka et al, 2009), German opaque complex verbs did give evidence of being decomposed by native speakers of German. One could hypothesize that this discrepancy is due to the task being used: Perhaps decomposition of opaque complex verbs was induced by the morphological priming technique (in which, e.g., a prime like reheat is followed by a target like heat) used in these studies.…”
Section: Cognate Verb Subdesign: Holistic Processing Of Opaque Complesupporting
confidence: 91%
“…For instance, Baayen, Levelt, Schreuder, and Ernestus (2008) examined the processing of regularly inflected nouns and showed that morpheme (lexeme) frequency can modulate participants' response speed in both word recognition and production. Lüttmann et al (2011a) tested the recognition and the production of derived German verbs with the cross-modal priming and the PWI paradigms. As compared with the unrelated baseline, a morphologically related distractor (prime) could facilitate target word processing significantly.…”
Section: Morphological Processing In Word Productionmentioning
confidence: 99%
“…In the following, we first review previous experimental evidence about the role of morphology in word recognition and production, and their implications on the development of language processing models (also see Lüttmann, Zwitserlood, & Bölte, 2011a). Next, we explain why it is important to consider the temporal dynamics of the activation of morphemic form and meaning in the present study.…”
Section: Introductionmentioning
confidence: 97%
“…Dual-route accounts assume morpheme-based processing for semantically transparent complex words (e.g., birdhouse), but (more) holistic processing for opaque words (e.g., hotdog). Most data that test such predictions come from comprehension studies, or from studies on the interface between comprehension and production, presenting complex words as distractors to pictures with monomorphemic names (e.g., Zwitserlood et al, 2002; Köster and Schiller, 2008; Lüttmann et al, 2011b; Verdonschot et al, 2012). To date, studies on the actual production of complex words are quite rare (e.g., Roelofs and Baayen, 2002; Lüttmann et al, 2011a; Jacobs and Dell, 2014).…”
Section: Introductionmentioning
confidence: 99%